Cape Verde Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
This Report on the Observance of Standards and Codes (ROSC) provides an assessment of the strengths and weaknesses of the existing financial reporting infrastructure that underpins financial accounting and auditing practices in Cape Verde. The assessment focuses on six pillars of financial reporting infrastructure: statutory framework, professional education and training, accountancy profession, accounting standards, auditing standards, and monitoring and enforcement of the applicable standards. The main purpose of this assessment is to assist the development and implementation of a country action plan for strengthening institutional capacity with attendant effects on enhancing corporate financial reporting in Cape Verde. The findings reveal that Cape Verde has recognized the importance of a strong corporate financial reporting architecture. In terms of accounting and auditing standards, Cape Verde adapted International Financial Reporting Standards (IFRS) for the private companies and fully adopted IFRS for banking and insurance institutions sector. However, there is no tradition of financial analysis in the country (except within the financial institutions when issuing credit) and no credit-rating agencies. The banks do not rely on corporate financial statements; generally, the lenders manage credit risks using collaterals. The Bank of Cape Verde mandated IFRS for banks and insurance companies in 2008. In addition, the capacity of regulators would be built to cope with the demands of IFRS-compliant financial reporting. The central bank would include in its scope the regulation of micro-finance institutions, which are currently unregulated. In order to improve the legal framework of corporate financial reporting, there is need to enact a Financial Reporting Act with focus on all regulatory aspects of accounting and auditing.